Effectiveness of Centella Asiatica (Pegagan) Spray Gel on Perineal Wound Healing in Postpartum Women - Salsabila, Nanda Lutfia; Fatmasari, Diyah; Wahyuni, Sri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Perineal wounds in postpartum mothers can potentially cause infections. The perineal area exposed to lochia and moisture creates an environment conducive to bacterial growth, thus hindering the wound healing process. Infections of perineal wounds can involve various types of bacteria that naturally colonize the skin and genital mucosa. The application of centella asiatica spray gel is one of the non-pharmacological methods for healing perineal wounds in postpartum mothers. This study aims to determine the effectiveness of applying centella asiatica spray gel 3 times a day with a concentration of 25% for 7 days on perineal wound healing and the growth of Staphylococcus aureus bacteria in postpartum mothers. This is a True Experimental study with a pretest–posttest control group design. Based on the inclusion criteria of second-degree perineal wounds with sutures were selected using random sampling, 17 participants to receive centella asiatica spray gel and 17 participants received standard dry-clean care. The level of wound healing was measured using the REEDA score. The growth of Staphylococcus aureus bacteria was measured using a colony counter. REEDA score data were analyzed using the Friedman and Mann-Whitney tests, while Staphylococcus aureus growth was analyzed using the Wilcoxon and Mann-Whitney tests. Based on the average decrease in REEDA scores by 1.06, the application of centella asiatica spray gel was effective for perineal wound healing (p=0.000). There was a significant difference in the average growth of S.aureus (p=0.040) in perineal wounds of postpartum mothers, with the intervention group showing an average difference of 6.34. The application of centella asiatica spray gel 3 times a day with a concentration of 25% for 7 days was effective for perineal wound healing and reducing Staphylococcus aureus growth in postpartum mothers.